Designing a Better Day: Adult Day Centers: Comparative Case Studies - (:unkn) unknown (My University, 2001)
The Adult Day Center (ADC) is emerging as a new and important social institution and place type in the continuum of care environments. Nine case studies representing the range of ADC's currently operating in the United States are considered from a holistic, systemic perspective. Each case is presented in terms of place profile, program, physical setting and "the place in use." The results are not a matter of ADC "best practices" or "good/bad" ways of doing things, but rather a method of identifying characteristics and components that appear to contribute to making a positive difference in the experience of adult day care.